Trade and employment in developing countries. - Krueger, Anne O. (University of Chicago Press, 1981)
This first book of a three-volume study examines the way trade policies in developing countries affect the level and composition of employment. There is special emphasis on the effects of import substitution policies that attempt to make a country self-sufficient by producing local substitutes for imports, as compared with policies that further the expansion of imports. Ten countries are studied: Brazil, Chile, Colombia, Indonesia, the Ivory Coast, Pakistan, South Korea, Thailand, Tunisia, and Uruguay. The contributors to the volume analyze the link between trade strategies and employment within a common framework, and the analyses of trade policy include the level and structure of protection, the relation of trade policy to labor demand, the labor intensiveness of trade, and the extent of distortions in factor markets and their effects on trade.